KOREKSI FISKAL, PEMERIKSAAN KEBERATAN DAN BANDING - Yoseph Agus (Media Riset Akuntansi, Auditing & Informasi, 2005)
Fiscal Correction (reconciliation), tax audit, an objection and an appeal are four related activities taxpayer have to understand fully. On the fiscal correction column, a taxpayer usually put all temporary and permanent differences in order to produce fiscal report as regulated by tax law of provision. This is not over yet. Once, a tax audit find irregularities within taxpayer books of accounts, the Director General of Taxes may issue a Tax Underpayment Assessment, an Additional Tax Underpayment Assessment, a Tax Overpayment Assessment, or a Nil Tax Assessment. A Taxpayer may file an objection with the Director of Taxes. There are only two decisions : rejection or acceptance. A taxpayer may only lodge an appeal with tax court after an Objection Decision has been issued by the Director General of Taxes.